Biosorptive removal of Nickel(II) from aqueous solution by Mangosteen shell activated carbon. (2021) - Anitha, D.; Ramadevi, A.; Seetharaman, R.
Abstract: The adsorption of heavy metal Ni (II) from aqueous solution by sulphuric acid modified agricultural byproduct mangosteen shell was studied. The effect of adsorbent dose, contact time, pH, on the removal efficiency of Ni (II) was evaluated by batch mode studies. At optimum experimental condition removal of nickel was observed at pH 5 and a carbon dosage of 60 mg. The surface morphology and functional groups were analyzed using FT-IR data and scanning electron microscope. Freundlich and Langmuir adsorption isotherm studies were performed. The adsorbent was noted to be economical and efficient in the removal of Ni (II) from aqueous solution.